2019
DOI: 10.1111/mec.15145
|View full text |Cite
|
Sign up to set email alerts
|

Tropical rainforest flies carrying pathogens form stable associations with social nonhuman primates

Abstract: Living in groups provides benefits but also incurs costs such as attracting disease vectors. For example, synanthropic flies associate with human settlements, and higher fly densities increase pathogen transmission. We investigated whether such associations also exist in highly mobile nonhuman primate (NHP) Groups. We studied flies in a group of wild sooty mangabeys (Cercocebus atys atys) and three communities of wild chimpanzees (Pan troglodytes verus) in Taï National Park, Côte d'Ivoire. We observed markedly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 74 publications
(124 reference statements)
3
49
0
Order By: Relevance
“…This suggests that perhaps the significance of filth flies in pathogen transmission has been underestimated. Gogarten et al () utilize molecular approaches to detect DNA from two pathogens, TPE, and Bacillus cereus biovar anthracis ( Bc bv a ), the causative agent of sylvatic anthrax on captured filth flies. While this method does not definitively incriminate the captured fly species as mechanical vectors, their approach in culturing Bc bv a to determine its viability on flies is laudable and demonstrates the possibility of sylvatic anthrax being transmitted by flies.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…This suggests that perhaps the significance of filth flies in pathogen transmission has been underestimated. Gogarten et al () utilize molecular approaches to detect DNA from two pathogens, TPE, and Bacillus cereus biovar anthracis ( Bc bv a ), the causative agent of sylvatic anthrax on captured filth flies. While this method does not definitively incriminate the captured fly species as mechanical vectors, their approach in culturing Bc bv a to determine its viability on flies is laudable and demonstrates the possibility of sylvatic anthrax being transmitted by flies.…”
mentioning
confidence: 99%
“…By exploiting the natural history of fly relationships with their surrounding ecosystem, molecular ecologists and entomologists can use flies as sentinels to address ecological and evolutionary knowledge gaps. (b) Gogarten et al () marked and tracked flies and found that a small number of marked flies stayed with primate social groups for up to 12 days and 1 km. This method is demonstrated here by flies with blue markings remaining near mangabey groups (blue circle) and flies with red markings remaining near chimpanzee groups (red circle).…”
mentioning
confidence: 99%
See 3 more Smart Citations